Globalization isn't in decline: It's changing - Erik Van der Marel (European Centre for International Political Economy (ECIPE), 2020)
Globalization isn't in decline; it is simply changing. Although the COVID-19 crisis has seen a dramatic decline in goods trade, investments and the movement of people, a new type of globalization is emerging. This "new globalization" is based on digital services, research and development, data, ideas, and other intangibles. This development has been going on for a while and have evolved more rapidly after the previous global financial crisis (GFC) in 2008-9. For instance, the GFC caused digital services trade to significantly "de-link" from goods-related services trade. This pattern illustrates that the COVID-19 crisis will likely mark another break in trade patterns and that future growth in globalization will depend crucially on digital trade and cross-border exchange in intangibles.
Keywords: 330; Coronavirus; Globalisierung; Strukturwandel; Digitalisierung